Cave Dwelling: the History and Cultural Inheritance in Contemporary Shanxi - Ding, Pengpeng; Pimpiset, Pitipong; Yamcharoen, Nattapong (International Journal of Natural Resources and Environmental Studies, 2024)
Shanxi cave dwellings are a unique habitat and cultural treasure of the Chinese nation, embodying the wisdom and life imprints of the people of the Loess Plateau. With ancient origins rooted in cave dwelling civilizations, Shanxi cave dwellings have evolved over millennia, gradually forming distinctive architectural styles and ways of life. These dwellings are not only the homes of Shanxi farmers but also the cradle of rich and diverse folk cultures deeply intertwined with the literary and artistic heritage of Shanxi. At the same time, their layout and structure reflect the social stratification and family concepts of the local society. With the onset of modernization, the impact of urbanization and new residential trends has posed unprecedented challenges to cave dwelling culture. To safeguard this precious intangible cultural heritage, both central and local governments have introduced a series of protection policies and implemented practical actions. More importantly, it is necessary to vigorously promote innovation and inheritance on the basis of protection, integrating cave dwelling elements into modern design, promoting cultural tourism experiences, and developing cultural and creative industries. This will revitalize this ancient and unique human habitat civilization in contemporary society, continuing the cultural confidence and national spirit of the Shanxi people.